Exploring Communication Challenges and Opportunities in Multicultural Teams - Sharapova, Valeriya; Pauknerová, Daniela, 1970-; Schmitt, Judith; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Multicultural teams are more prevalent in today's international corporate climate, giving firms the chance to benefit from different viewpoints and skill sets. However, managing such teams poses particular difficulties, especially communication problems. The obstacles managing people efficiently in multicultural teams are explored in this bachelor's thesis. Organizations may improve team performance, encourage diversity and inclusion, and ultimately gain a competitive edge in the global market by understanding the challenges of managing multicultural teams. This study combines theoretical work on multicultural teams that sheds light on the complex dynamics of managing human resources to minimize challenges and maximize opportunities, and from a practical perspective provides qualitative research into the real-life performance of such teams through team leader interviews. The results will show the application of theoretical knowledge to real examples of working in multinational teams, as well as useful recommendations for managing multicultural teams.
Vedoucí práce: Daniela Pauknerová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses